2016
DOI: 10.1155/2016/3924858
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of Human Mesenchymal Stem Cells to Enhance Their Regulation of the Immune Response

Abstract: Mesenchymal stem cells (MSCs) have attracted the attention of researchers and clinicians for their ability to differentiate into a number of cell types, participate in tissue regeneration, and repair the damaged tissues by producing various growth factors and cytokines, as well as their unique immunoprivilege in alloreactive hosts. The immunomodulatory functions of exogenous MSCs have been widely investigated in immune-mediated inflammatory diseases and transplantation research. However, a harsh environment at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
136
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 72 publications
3
136
0
2
Order By: Relevance
“…Increasing Evidence have demonstrated that pre-conditioning could enhance the therapeutic effects of MSCs. 55,56 Compared to in vivo inflammatory licensing by the recipient environment alone, in vitro inflammatory licensing prior to clinical use could enhance the immunomodulatory ability of MSCs exposed to inflammatory macrophages and secretome from primed MSCs possessed biologically active. 57 TLR4 activation by LPS stimulation could enhance the paracrine capacity of BMSCs, releasing large amounts of cytokines and exosomes, to represent a physiologically significant mechanism for tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing Evidence have demonstrated that pre-conditioning could enhance the therapeutic effects of MSCs. 55,56 Compared to in vivo inflammatory licensing by the recipient environment alone, in vitro inflammatory licensing prior to clinical use could enhance the immunomodulatory ability of MSCs exposed to inflammatory macrophages and secretome from primed MSCs possessed biologically active. 57 TLR4 activation by LPS stimulation could enhance the paracrine capacity of BMSCs, releasing large amounts of cytokines and exosomes, to represent a physiologically significant mechanism for tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…The cargo of USMSC-EVs in this study contained many chemokines (CXCL5, CCL3, CCL4, CCL11, CCL20), which might attract immune cells to the site of injury. However, research has strongly shown that MSCs primed with pro-inflammatory cytokines (IFN-γ, TNF-α, IL-1β) show enhanced immunosuppressive abilities [14,[21][22][23]. Specifically, research using EVs secreted from pro-inflammatory primed MSCs has shown positive immunosuppressive effects by polarising pro-inflammatory immune cells into anti-inflammatory immune cells in vitro [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…This study found no significant difference in growth kinetics of protein cargo between UCMSCs grown in normoxia and hypoxia, and research was divided on whether hypoxia has a stimulatory [30] or inhibitory [31,32] effect on MSC proliferation; albeit studies varied between the use of 1%-5% O 2 . Some groups have advocated for the use of hypoxia when growing cells in culture as it more closely mimics the oxygen levels that MSCs are exposed to in vivo [22], with neonatal-derived tissues rarely exceeding 5% in vivo [23]. The lack of change in growth may be because the cells were first isolated under normal oxygen (21%) conditions, and exposure to low oxygen (5%) at an earlier stage may be an influencing factor in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that proinflammatory stimulation may have prolonged effects on the function of MSCs. MSCs preconditioned by transient exposure to inflammatory cytokines alone or combined with PAMP enhanced immunomodulation and tissue regeneration (10)(11)(12). We recently observed that when MSCs were exposed to LPS repeatedly, NF-kB activation was significantly increased compared with single LPS exposure (13).…”
mentioning
confidence: 99%